Assessing the usefulness of the Little Developmental Coordination Disorder Questionnaire-Chinese in Chinese preschoolers: a sex-and age-specific analysis - Hua, Jing; Rihtman, Tanya; Peng, Yongmei; Wang, Tianjing; Su, Yuantao; Du, Wenchong (Frontiers in Psychology, 2024)
Aim: This study evaluated the sex-and age-specific usefulness of the Little Developmental Coordination Disorder Questionnaire-Chinese (LDCDQ-CH) in Chinese preschoolers. Method: A population-based sample of 51,110 children aged 3-5 years was recruited. Internal reliability, construct validity, concurrent validity with the Ages and Stages Questionnaire-third edition (ASQ-3), and discriminant validity with the Movement Assessment Battery for Children-second edition (MABC-2) were assessed. Age and sex effects on LDCDQ-CH scores were analyzed using ANOVA and t-tests. Results: The LDCDQ-CH exhibited excellent internal consistency and reliability across ages and genders. Confirmatory factor analysis supported the 15-item model's satisfactory fit. Positive and significant correlations were observed between LDCDQ-CH and ASQ-3 scores, indicating robust concurrent validity. Significant associations were found between LDCDQ-CH and MABC-2 scores. Higher scores were observed in older children and girls, indicating age-and sex-related differences in motor functional performance.The LDCDQ-CH is a reliable and valid tool to support early identification of motor coordination difficulty in Chinese preschoolers, and guiding interventions.Findings support its use across ages and genders, highlighting its potential in the Chinese context. Age-and sex-specific norms are needed for enhanced clinical applicability.